Effect of LiF addition on phase structure and piezoelectric properties of (Ba, Ca)(Ti, Sn)O3 ceramics sintered at low temperature. Issue 3 (April 2015) - Zhou, Peng-Fei; Zhang, Bo-Ping; Zhao, Lei; Zhu, Li-Feng
Abstract: In this study, a series of (Ba0.95 Ca0.05 )(Ti0.90 Sn0.10 )O3 – x LiF (BCTS– x LiF) (0≤ x ≤6 mol%) lead-free piezoceramics were fabricated by a conventional solid-state reaction method. The incorporation of LiF could significantly improve the sinterability of BCTS ceramics by reducing the sintering temperature from 1480 °C to 1250 °C, where a relative density over 90% was achieved with grown grains of 5–20 μm. X-ray diffraction and Raman spectroscopy experiments revealed that BCTS– x LiF ceramics are composed of coexisting R – O – T phases at 0≤ x ≤1 and R – T phases at 2≤ x ≤6 at room temperature. Optimal piezoelectric properties of d 33 =510 pC/N, k p =40.9%, ε r =5370, tan  δ =0.019 and d S /d E =961 pm/V were obtained at x =5, which is attributed to the coexistence of R and T phases with an optimum ratio at room temperature and dense structure with large grains.